BEYOND THE OFFICIAL PHOTOGRAPH: COMPARATIVE STUDY OF MEDIA AND PARTY PORTRAITS OF INDIAN WOMEN POLITICIANS - Naqvi, Lubna Sadaf; Chhura, Bikashdev; Sharma, Aarti; Sharma, Bhavana; Agarwala, Sumit; Verma, Amit (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In modern democracies, political portraits are quite important in the development of the perception of the populace regarding leadership, legitimacy and gender. This paper analyzes the visual representation of Indian women politicians under three types of regimes, namely, official, party, and media, which are ruled by various institutional, ideological and journalistic logics. Going beyond the analysis of isolated images, the study uses the comparative framework including the visual content coding, the regime-based analysis, and the evaluation based on the case studies. A data collection of publicly available portraits was collected through a structured coding scheme that comprises of setting, pose, affect, symbolism, textual elements, and personalization. The results indicate systematic differences at the regime level: institutional power and disinterest are highlighted in official portraits, ideological symbolism and collective identity are in the foreground of party portraits, and personalization, dramatization, and emotional expressiveness are prioritized in media portraits. Cases allow also revealing that identical political players are graphically re-created even between regimes, and reveal a stable trade-off between power and personalization. This research is important to visual politics and gender studies by providing a regime-specific approach of analyzing how political imagery reproduces negotiation of gendered leadership stories. The findings highlight the importance of considering visual analysis as a unified part of political communication studies and have a base to conduct cross-national, longitudinal, and computational research of political representation.